Ethyl 2-(2-acetoxybenzylidene)-7-methyl-3-oxo-5-phenyl-2,3-dihydro-5H-1,3-thia zolo[3,2-a]pyrimidine-6-carboxylate - Jotani, M.M.; Baldaniya, B.B.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
In the title molecule, C(25)H(22)N(2)O(5)S, the atoms of the thiazolopyrimidine ring system, with the exception of the phenyl-bearing C atom [deviation = 0.177 (2) angstrom], are essentially planar [r.m.s deviation = 0.100 (2)degrees] and the mean plane of these atoms forms dihedral angles of 89.86 (10) and 7.97 (8)degrees with the phenyl and benzene rings, respectively. In the crystal, co-operative C-H center dot center dot center dot O and C-H center dot center dot center dot pi interactions lead to a supramolecular chain along the a axis. These chains are connected via pi-pi interactions [centroid-centroid = 3.7523 (13) angstrom]